Transanal Endorectal Pull Through Versus Laparoscopic Assisted Transanal Endorectal Pull-Through Procedures For Short Segment Hirschsprung’s Disease (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The main goal in the treatment of patients with Hirschsprung’s disease is resection of the aganglionic segment and pull down the normo-ganglionic bowel. The aim of the study was to compare the efficacy and safety of outcome following Laparoscopic Assisted Transanal Endorectal Pull through (LATEP) and transanal endorectal pull through procedures for short segment Hirschsprung’s Disease.Materials and methods: This quasi-experimental study was conducted at the Department of Pediatric Surgery in  Chittagong Medical College Hospital (CMCH)  Chattogram from June 2021 to june 2023. All the patients diagnosed as a case of a short segment Hirschsprung disease either by Barium enema or colonic/rectal biopsy with or without colostomy irrespective of age and sex were included. Total 18 patients were included in this study: Group- A laparoscopicassisted trasnanal endorectal pull through and Group- B transanal endorectal pull through which were randomly selected.Results: No post-operative enterocolitis, postoperative adhesive bowel obstruction, incontinence was seen. Pain was   more in trans anal endorectal pull through group than laparoscopic trans anal endorectal pull through group, pain scores 6.71 vs 5.0 respectively. In comparison of LATEP, readmission and other complication such as constipation, stricture rates were lower from TEPT LATEP offered several advantages, including an early visualization of the colon to identify the position of normal innervation and a direct visualization of the colon at the time of pull- through, therefore  barring the  threat of bowel twisting and muscle cuff folding and postoperative adhesive obstruction.Conclusion: Both procedures were safe and effective with LATEP having some added advantages.   JCMCTA 2025 ; 36 (1) : 61-65